The Cohomology Groups of Real Toric Varieties Associated with Weyl Chambers of Types C and D - Choi, Suyoung; Kaji, Shizuo; Park, Hanchul (Proceedings of the Edinburgh Mathematical Society, 2019)
Given a root system, the Weyl chambers in the co-weight lattice give rise to a real toric variety, called the real toric variety associated with the Weyl chambers. We compute the integral cohomology groups of real toric varieties associated with the Weyl chambers of type Cn and Dn, completing the computation for all classical types.
Keywords: cohomology; generalized Euler number; poset topology; real toric variety; root system; Weyl chamber